Different factors modulate visceral and subcutaneous fat accumulation in adults: a single-center study in Brazil - Chagas, Camila Lima; da Silva, Nadja Fernandes; Rodrigues, Isa Galvão; Arcoverde, Gabriela Maria Pereira Floro; Ferraz, Victoria Domingues; Sobral Filho, Dário Celestino; Diniz, Alcides da Silva; Pinho, Cláudia Porto Sabino; Cabral, Poliana Coelho; de Arruda, Ilma Kruze Grande (Frontiers in Nutrition, 2025)
BackgroundAbdominal adipose tissue consists of visceral and subcutaneous fat deposits, each with unique metabolic and functional properties. Identifying the characteristics that influence different obesity phenotypes can support targeted prevention and intervention strategies.ObjectiveTo identify predictive factors associated with visceral and subcutaneous adipose tissue accumulation.MethodsThis is a cross-sectional study including adults of both sexes aged ≥20 years under outpatient care in a public healthcare service in Northeast Brazil. Visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) were measured via ultrasound. Anthropometric, clinical, sociodemographic, and behavioral variables were incorporated into the predictive model.ResultsA total of 347 individuals were included. They were median age of 47.0 years (interquartile range: 39.0 to 56.0). Visceral obesity was found in 79.3% of the sample. Adjusted analysis demonstrated that physical inactivity (OR 2.3; 95% CI 1.1–4.7; p = 0.023) and elevated waist circumference (WC) (OR 6.4; 95% CI 2.6–15.8 p < 0.001) were associated with VAT accumulation. Alcohol consumption increased the likelihood of SAT accumulation by 2.2 times (95% CI 1.3–3.7; p = 0.005), while elevated WC raised this likelihood by 4.5 times (95% CI 2.1–9.8; p < 0.001). The VAT/SAT ratio was significantly higher in older adults (OR 5.5; 95%CI 2.0–14.8; p = 0.001), among individuals of Mixed Race and Black, those with lower educational levels (OR 2.4; 95%CI 1.1–5.2; p = 0.028), and in diabetics (OR 2.4; 95%CI 1.2–4.9; p = 0.017).ConclusionDistinct factors influence visceral and subcutaneous obesity. Sedentary behavior emerged as an independent predictor of visceral obesity, while alcohol consumption was associated with a subcutaneous obesity pattern. Diabetes and sociodemographic factors (older age, non-White race, and lower education) were predictive of an elevated VAT/SAT ratio.